Ergonomic Risk Evaluation of Telecommunication Tower Workers Based on SNI 9011:2021: A Case Study at a Telecommunication Service Company - Akbar Hanifanur Prayitno; Doni Hikmat Ramdhan (International Journal Labs, 2026)
Work-related musculoskeletal disorders (WMSDs) are a major concern in telecommunication tower work, which commonly involves manual material handling and non-neutral postures. This study aimed to evaluate the ergonomic risk among telecommunication tower workers using the Indonesian National Standard (SNI) 9011:2021. A quantitative observational cross-sectional study was conducted among 33 workers (total sampling). Data were collected through a WMSD symptom questionnaire, field observations using an ergonomic hazard checklist (including estimated exposure duration), and an assessment of manual lifting/handling in accordance with the SNI components. Risk scores were calculated by summing the upper-body score, back and lower-body score, and manual handling score, then categorized as follows: ?2 (safe), 3–6 (needs further monitoring), or ?7 (hazardous). Most respondents were installers (72.7%), with the largest proportion having 4–6 years of work tenure (39.4%). Observations identified 14 ergonomic hazards present in 100% of workers, mainly related to upper-body demands and repetitive activities, with some exposures occurring for 25–50% of the work shift. Total risk scores ranged from 12 to 24 (mean 19.36 ± 2.22), placing all workers (100%) in the hazardous category. The main contributors were manual handling (mean 8.70 ± 1.93; 87.9% ?7) and upper-body exposure (mean 7.67 ± 1.49; 57.6% ?7). Priority ergonomic controls are required to reduce manual material handling and overhead work through combined engineering and administrative measures, supported by periodic SNI-based monitoring.